Identification of larval morphotypes of helicoverpa armigera (Hiibner) (Lepidoptera: noctuidae) and their characterization using molecular markers - Ranjith M T (Department of agricultural entomology, College of horticulture, 2015)
Helicoverpa armigera (Hübner) is a highly destructive, polyphagous pest inflicting sizeable damage in economically important crops worldwide. Notoriety of H. armigera is characterized by the ability to thrive in different crop ecosystems, high mobility, fecundity and great capacity to develop resistance to synthetic insecticides used in its management. The presence of larval morphotypes in different crop ecosystems is another feature of this pest. Colour morphs reportedly exhibit differential susceptibility against different insecticides indicating the presence of strong genetic variability with an adaptive significance for the insect. Thus, phenotypic and genetic variability studies could yield valuable information on population structure that can be useful in evolving appropriate strategies for management of genetically distinct morphotypes. A study was therefore envisaged to identify larval morphotypes of H. armigera on preferred hosts and to characterize these morphotypes using molecular markers. Surveys were conducted in vegetable growing areas of Palakkad, Thrissur, Kasaragod and Thiruvananthapuram districts in Kerala, as well as flower growing area of Thovalai, Tamil Nadu during the period between 2012 and 14. The larval populations collected from tomato in Palakkad and also from okra, chickpea, amaranthus and tomato in Thrissur were subjected to morphological as well as molecular level studies. Studies on larval prothoracic setal arrangement, structure of male genitalia and DNA barcoding confirmed the identity of the test insect as H. armigera. Twenty two larval morphotypes were identified from four host plants viz., tomato (7), okra (6), amaranthus (5) and chickpea (4) and the frequency of larval morphotypes on each crop were calculated. The dominant morphotypes observed were green on tomato, yellowish green on okra, green with green longitudinal lines on chickpea and green with dark longitudinal lines on amaranthus. Most of the larvae collected from tomato, chickpea and amaranthus possessed continuous pigmentation on lateral bands whereas those collected from okra were without pigmentation on lateral bands. The intensity of black pigmentation on thoracic and last i abdominal segments of morphotypes was worked out based on a standard scale (0-4) and the intensity varied among morphotypes with black pigmentation. The morphometric parameters of larva, pupa and adult were recorded and these showed significant difference among morphotypes on different crops. Further, the morphometric parameters were used for constructing morphocluster based on multivariate analysis techniques and it yielded two major clusters with sixteen morphotypes and six morphotypes in first and second clusters respectively. Genomic DNA was isolated from twenty two larval morphotypes using modified CTAB method, amplified with selected eight H. armigera specific SSR primers, resolved in poly acrylamide gel (10%) and visualized in silver stain (2%). The clear and distinct bands produced were further used for developing DNA fingerprint for individual larval morphotypes. Based on the presence or absence of bands, Dice coefficient of similarity was worked out and the coefficient ranged from 0.55 to 1.00. Dendrogram deduced from similarity coefficient yielded two major clusters and cluster analysis revealed that the morphotypes occurring on vegetables stood together in one cluster, whereas those occurring on chickpea stood out separately in another cluster. Analysis of gut microbiota of larva showed the presence of bacteria belonging to 173 families which helps the insect for its better survival. The twenty two larval morphotypes observed on four host plants were highly specific with respect to body colour and morphometric parameters. Further, molecular level analysis confirmed the existence of genetic difference among the morphotypes. Hence, present findings suggest that even though H. armigera is a polyphagous pest, it could have evolved into different larval morphotypes with great affinity to specific hosts. This could be an adaptive strategy of the pest to reduce intra specific competition and there by ensure better survival on host plants.